Functionality of Information Technologies Supporting Knowledge Sharing in Organization - Torończak, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The majority of global corporations become „knowledge companies” - companies where knowledge becomes one of the most valuable assets. Rapid development of computer networks supported by expansion of Internet allow companies to exchange knowledge without geographical limits. Knowledge management in organizations may be divided in six key competencies: identification, acquisition, development, sharing, utilization, and retention of knowledge. The article focuses on knowledge sharing and distribution as a key process that supports companies’ effective development. Latest technologies and Internet development gave possibilities to create hardware and software innovations capable of almost full support of knowledge sharing and distribution. Instant communicators, VoIP and web mash-up technologies are just few samples. Lack of geographical restraint requires a new approach of designing knowledge sharing systems. The new approach suggests building systems adjusted to IT systems complexity and data diversification present in organizations. Taking it to consideration, supported with proper corporate culture, adjusted IT infrastructure and standardization of data formats may result in good choosing of knowledge sharing and distribution system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 142-151